Maternal red blood cell alloantibodies identified in blood samples obtained from Iranian pregnant women: the first population study in Iran. Issue 1 (7th November 2016) - Shahverdi, Ehsan; Moghaddam, Mostafa; Gorzin, Fateme
Abstract : BACKGROUND: The objective was to determine the frequency of occurrence of alloantibodies among pregnant women in Iran. STUDY DESIGN AND METHODS: This was a prospective cross‐sectional study, which was carried out in the immunohematology reference laboratory of the Iranian Blood Transfusion Organization in Tehran, Iran, in 2008 to 2015. Screening and identification of red blood cell (RBC) alloantibodies was done on the sera of 7340 pregnant females using the standard tube method and gel column agglutination technique. RESULTS: Alloantibodies were identified in the serum of 332 of the 7340 (4.5%) pregnant women. A total of 410 antibodies were detected in 332 positive maternal serum samples with no previous history of blood transfusion. Anti‐D was the most common antibody accounting for 70.5% of all the antibodies formed in D– women. The incidence of specific alloimmunization other than Rh group was 14.4%. CONCLUSION: We concluded that the alloimmunization rate was high in comparison with wide pattern in previous studies. In Iran, like other developing countries, alloimmunization screening tests are performed only to detect anti‐D in pregnant D– women. This high rate of alloimmunization, quite possibly, is due to the fact that the majority of blood samples came from pregnant women known to have previous obstetric problems. However, we suggest that RBC antibody screening tests should be extended to all D+ women.